MED13L loss‐of‐function variants in two patients with syndromic Pierre Robin sequence. Issue 1 (21st November 2017) - Gordon, Christopher T.; Chopra, Maya; Oufadem, Myriam; Alibeu, Olivier; Bras, Marc; Boddaert, Nathalie; Bole‐Feysot, Christine; Nitschké, Patrick; Abadie, Véronique; Lyonnet, Stanislas; Amiel, Jeanne
Abstract : We report two unrelated patients with Pierre Robin sequence (PRS) and a strikingly similar combination of associated features. Whole exome sequencing was performed for both patients. No single gene containing likely pathogenic point mutations in both patients could be identified, but the finding of an essential splice site mutation in mediator complex subunit 13 like ( MED13L ) in one patient prompted the investigation of copy number variants in MED13L in the other, leading to the identification of an intragenic deletion. Disruption of MED13L, encoding a component of the Mediator complex, is increasingly recognized as the cause of an intellectual disability syndrome with associated facial dysmorphism. Our findings suggest that MED13L –related disorders are a possible differential diagnosis for syndromic PRS.